Radar ad alta risoluzione nelle procedure di controllo della nuova Polotica Agraria Comunitaria - Monaldi, Giulio; Rossi, Livio; Guerra, Pierpaolo (GEOmedia, 2009)
New VHR SAR data for control procedures in Agriculture The new VHR SAR data generation has renewed both the technological expectations and the data policy for using radar in Agriculture solving previous problems related to this technology. AGEA, with ASI (Italian Space Agency) collaboration, addressed its activities to satellite SAR preoperational feasibility in Controls with Remote Sensing (CwRS), Object of the work were: crop detection capability, geometric accuracies, operational scales, usability in replacing optical affected by cloud cover and agro-environmental parameters with indicators extraction.